Increases in use of Medicare Benefits Schedule mental health items among women who gave birth in New South Wales, 2009-2015 - Nicole Reilly; Nicholas Egan; Marie‐Paule Austin; Peta M. Forder; Deborah Loxton (Elsevier, 2022)
Abstract Objective: To report rates of Medicare Benefits Schedule (MBS) mental health item use among a sample of women who gave birth in NSW (2009‐2015) and examine if the SAFE START policy increased use of these items among perinatal women. Methods: Data was drawn from women participating in the Australian Longitudinal Study on Women's Health 1973‐1978 cohort, linked to data from the NSW Perinatal Data Collection and MBS. Results: Use of Medicare‐subsidised mental health items increased 2.7‐fold among perinatal women (n=1,453) between 2009 and 2015 (4.1% versus 11.0% respectively), compared to a 1.3‐fold increase among non‐perinatal women (n=1,800, 6.3% versus 8.4% respectively). However, the increased use of MBS mental health items among perinatal women was not observed to be impacted by the SAFE START policy, after accounting for time trends. Conclusion: There was a substantial increase in the use of MBS mental health items among women in NSW between 2009 and 2015, with a more pronounced increase among women who had given birth compared to those who had not. Implications for public health: This study provides important information about changes in mental health service use during a time of significant investment in perinatal mental health, and demonstrates the value of longitudinal survey data linked with administrative health data to evaluate the impact of health policy.